2002
DOI: 10.1051/0004-6361:20020653
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence of simulated interstellar matter after gamma-ray irradiation

Abstract: Abstract. Interstellar matter is known to be strongly irradiated by cosmic radiation and several types of cosmic ray particles. Simulated interstellar matter, such as synthesized forsterite (Mg 2 SiO 4 ), enstatite (MgSiO 3 ) and magnesite (MgCO 3 ), has been irradiated with 60 Co gamma-rays in liquid nitrogen, and also irradiated with fast neutrons at 10 K and 70 K by making use of the low-temperature irradiation facility of the Kyoto University Reactor (KUR-LTL. Maximum fast neutron dose is 10 17 n f /cm 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
1
18
1
1
Order By: Relevance
“…It comes from dense regions of the interstellar medium, like the Red Rectangle. Ledoux et al (2001) have explored laboratory photoluminescence of silicon nanoparticles as a promising candidate, while Koike et al (2002) prefer thermoluminescence from silicates like forsterite irradiated by cosmic rays. Crystalline silicates are optically anisotropic (Suto et al 2002).…”
Section: Dust and Ashesmentioning
confidence: 99%
“…It comes from dense regions of the interstellar medium, like the Red Rectangle. Ledoux et al (2001) have explored laboratory photoluminescence of silicon nanoparticles as a promising candidate, while Koike et al (2002) prefer thermoluminescence from silicates like forsterite irradiated by cosmic rays. Crystalline silicates are optically anisotropic (Suto et al 2002).…”
Section: Dust and Ashesmentioning
confidence: 99%
“…Recently, we have suggested that thermoluminescence spectra of forsterite after y-ray irradiation are very similar to the ERE of the Red Rectangle nebula (Koike et al, 2002). In this paper, we will investigate this possibility in more detail.…”
Section: Introductionmentioning
confidence: 86%
“…This feature is common to all bulk samples and powder ones. In addition, in the case of bulk samples, other weak peaks at 590, 595, and 705 nm also appeared (Koike et al, 2002).…”
Section: Luminescence Of Forsterite and Enstatitementioning
confidence: 92%
See 1 more Smart Citation
“…Many candidates for the carrier have been proposed, for example, polycyclic aromatic hydrocarbons (d 'Hendecourt et al 1986, PAHs), quenched carbonaceous composite (Sakata et al 1992, QCC), hydrogenated amorphous carbon (Furton & Witt 1992, HAC), carbon clusters (Seahra & Duley 1999), crystalline silicon nanoparticles (Ledoux et al 2001), nanodiamonds (Chang et al 2006), and doubly ionized PAH ions (divalent cations) . Koike et al (2002) have also suggested that the ERE is caused by thermoluminescence of silicates. Ledoux et al (1998Ledoux et al ( , 2001 showed that crystalline silicon nanoparticles have a high-PL quantum yield compared with other candidate materials and that the PL quantum yield is a very significant physical constraint for candidate materials.…”
Section: Introductionmentioning
confidence: 99%